2020
DOI: 10.3390/pr8080949
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical and Biochemical Parameters of Petrol-Contaminated Soil after Biostimulation with an Enzyme Reagent

Abstract: This study aimed to assess the effect of petrol and the Fyre Zyme reagent on selected chemical and biochemical properties of loamy sand. The experiment was conducted under laboratory conditions. First, petrol was introduced into the soil at doses of 0 and 50 g k−1dry matter (DM). Next, 6% Fyre-Zyme enzyme reagent solution was added to the samples contaminated and uncontaminated with petrol, in the following combinations: 0 (control), once at 40 cm3 kg−1 DM, twice at 20 cm3 kg−1 DM at two-week intervals, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The activity of the enzymes in the soil that was not exposed to [TBP][Br] remained at a similar level during the experiment ( Table 2 ). This is in line with the results of our earlier study, in which no significant changes were found in the activity of enzymes over time in uncontaminated soil [ 7 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultssupporting
confidence: 93%
“…The activity of the enzymes in the soil that was not exposed to [TBP][Br] remained at a similar level during the experiment ( Table 2 ). This is in line with the results of our earlier study, in which no significant changes were found in the activity of enzymes over time in uncontaminated soil [ 7 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultssupporting
confidence: 93%
“…Because it is feasible to only cultivate a fraction of soil microbiota [ 15 ], it seems essential to determine the biological activity of soil by assaying its enzymatic activity [ 73 , 74 ]. The soil enzymes are perceived as reliable soil quality indicators [ 17 , 75 , 76 ]. They are used to construct models for the assessment of potential soil fertility [ 28 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although more rarely used to determine pollution’s effect on the soil ecosystem’s stability, also such enzymes as catalase, β-glucosidase, urease, phosphatases, and arylsulfatase can provide valuable information on the metabolic capability of soil [ 73 , 74 , 83 ]. Their indicatory potential is due to the strong association of their activities with biogeochemical cycles of C, N, P, and S [ 71 , 75 ]. Our study has emphasized the significant effect of cocksfoot and petrol on C, N, and P metabolism in the soil, as evidenced by the changes in the population numbers and diversity of microorganisms as well as in activities of the soil enzymes tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the ecosystem in which they are found, pollutants may undergo slow transformations resulting from various chemical, physical, and biological processes. Highly toxic soil pollution may result in the disappearance of organisms, thus disabling the self-purification process of the soil environment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%